Mesoporous silica encapsulating ZnS nanoparticles doped Cu or Mn ions for warning clothes - Amina L. Mohamed; Tawfik A. Khattab; Mohamed F. Rehan; Ahmed G. Hassabo (Results in Chemistry, 2023)
Mesoporous nanocapsules originated from silica encapsulated ZnS doped with metal oxide (Cu or Mn) were assembled and characterized. The morphological characterization was performed using Fourier-transform infrared spectroscopy (FTIR), UV–visible absorption spectra, and transmission electron microscopy (TEM). The analyses findings proved the structures of the synthesized metal oxide nanoparticles. It was verified that those metal nanoparticles are doped in the silica mesopores with an average particle size of 10–50, 30, 40, and 200 nm for ZnS, Zn doped Cu+2, Zn doped Mn+2, and silica, respectively. The morphological characterization of the cotton fabrics treated with the prepared mesoporous nanocapsules has been carried out by scanning electron microscopy (SEM). The mechanical and physical properties, antibacterial activity, and UPF measurements were also explored. The analyses results confirmed that the silica-encapsulated ZnS doped with metal ions imparts excellent antibacterial activity and ultraviolet protection to the cotton fabric that is distracted by physical or mechanical properties.